2010
DOI: 10.1016/j.ejcts.2010.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Slower progression of atherosclerosis in vein grafts harvested with ‘no touch’ technique compared with conventional harvesting technique in coronary artery bypass grafting: an angiographic and intravascular ultrasound study

Abstract: The superior long-term patency rate using the NT vein-graft technique at CABG could be explained by a significantly slower progression of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 21 publications
2
51
1
1
Order By: Relevance
“…Given that saphenous vein is an autologous transplanted organ, harvest and preparation manipulations should be designed to minimize injury, which may lead to reduced intimal hyperplasia and improved clinical outcomes. 6,7 …”
mentioning
confidence: 99%
“…Given that saphenous vein is an autologous transplanted organ, harvest and preparation manipulations should be designed to minimize injury, which may lead to reduced intimal hyperplasia and improved clinical outcomes. 6,7 …”
mentioning
confidence: 99%
“…Johansson et al [2] conducted a randomised-controlled trial of 104 patients with SV grafts harvested by the conventional technique (CT) and the no-touch technique (NT), analysing graft patency rates with focus on early atherosclerotic changes. In the short-term study (18 months) stenosis was observed in 11.0% of grafts in the NT-group versus 25.0% in the CT-group (P=0.006).…”
Section: Resultsmentioning
confidence: 99%
“…Johansson et al conducted a randomized controlled trial of 104 patients with LSV grafts harvested by either a COT or NT technique. The primary outcome measures were graft patency rates, intimal thickness and degree of intimal hyperplasia at 18 months (short‐term) and 8.5 years (long‐term) postoperatively, with a focus on cineangiographic‐evaluated stenosis.…”
Section: The No‐touch Techniquementioning
confidence: 99%